2013
DOI: 10.1590/s0100-83582013000300003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of weed interference on soybean cultivars at two sowing times

Abstract: -This study aimed to evaluate the effects of weed interference on soybean cultivars at two sowing times in Urutaí, GO. The treatments were arranged in split-plots, and the sowing times (November 16 and December 16, 2009) were allocated in the plots; the soybean cultivars [BRSGO Amaralina, P98C81 (semi-late cycle) BRSGO Raissa, BRSGO Indiara, P98Y11 (median cycle) and BRSGO 7560, BRSGO Caiapônia, Emgopa 302RR (early cycle)] were allocated in the split-plots; and the coexistence or non coexistence of soybean cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…In other words, soybean seed yield was reduced by 22% in un-weeded treatment compared with the WCH+WCHW treatment. Marangoni et al (2013) reported that soybean seed yield was reduced by 30% due to weed competition. SEYED Z. HOSSEINI, SAEED FIROUZI, HASHEM AMINPANAH and HAMID R. SADEGHNEJHAD…”
Section: Seed Yieldmentioning
confidence: 99%
“…In other words, soybean seed yield was reduced by 22% in un-weeded treatment compared with the WCH+WCHW treatment. Marangoni et al (2013) reported that soybean seed yield was reduced by 30% due to weed competition. SEYED Z. HOSSEINI, SAEED FIROUZI, HASHEM AMINPANAH and HAMID R. SADEGHNEJHAD…”
Section: Seed Yieldmentioning
confidence: 99%
“…However, results for weedy canopy did not significantly differ from of the mechanically weeded. According to research done by Marangoni et al (2013), weed management had a significant effect of on grain yield of soybeans. The yield of soybean in the absence of coexistence with weeds (weeded) was higher compared to the yield of soybean in coexistence (unweeded) with weeds.…”
Section: Grain Yield (G/plot)mentioning
confidence: 99%
“…If weeds are not controlled, it will not only interfere with the growth and crop yield, but will also increase the production cost due to the increase in labour costs, agricultural inputs or machinery. According to the study by Marangoni et al (2013), weed management (weeded, unweeded) greatly influenced soybeans yield. The effect of weed management on different soybean varieties was studied and positive and negative effects on yields were found depending on varieties.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the weeds of the species Galinsoga parviflora, Digitaria horizontalis, Brachiaria decumbens, Amaranthus retroflexus, Bidens pilosa, Euphorbia heterophylla and others, in competition with soybeans throughout the crop cycle, reduced the grain yield by 30% (Marangoni et al, 2013). Soybean in competition with maize that emerged ten days earlier than or on the same day produced an average of 382% and 241% less than when maize emerged ten days after the crop (Piasecki, 2015).…”
Section: Evaluationsmentioning
confidence: 99%